The other of myself: representations of portuguese teachers about intercultural education related concepts - Prata Gomes, Miguel (2016)
Having into consideration that we live in a multicultural society, it is important to analyse how far people view and accept each other. Therefore, one should reflect upon concepts such as: representations and stereotypes, because they are interpersonal constructs which are (re)built during the interaction of different sociocultural groups. In this study, we focus our attention on the representations a sociocultural group – Portuguese teachers - has of intercultural education and the role of teachers and educators in the promotion of an intercultural approach at school. We believe that teachers have the responsibility to: find out the representations students have of the Other; reconfigure stereotyped representations; and create representations which favor dialogue and relationship with the Other flourish. Following a sociolinguistic approach (Müller, 1998; Vasseur, 2001; Vasseur & Hudelot, 1998), which is related to the construction and diffusion of representations in discourse, we analyse the discourse of teachers during a workshop called ‘The Other and Myself’, in which they build and discuss about a didactic mask that portrays their own vision of both themselves and their ideas of intercultural education.